To rewrite the equation \( C = 17D + 16 \) in terms of the dependent variable \( D \), we need to solve for \( D \).
Starting with the original equation:
\[ C = 17D + 16 \]
- Subtract 16 from both sides to isolate the term with \( D \):
\[ C - 16 = 17D \]
- Now, divide both sides by 17 to solve for \( D \):
\[ D = \frac{C - 16}{17} \]
Now, let's match this with the provided responses:
- D = 17C β 16 (incorrect)
- D = \frac{1}{7}C β 16 (incorrect)
- D = 7(C + 16) (incorrect)
- D = 17C + 16 (incorrect)
- D = 7(Cβ16) (incorrect)
None of the options given seem to match the correct equation \( D = \frac{C - 16}{17} \).
It seems like there may be a misunderstanding in the options provided. If we had the correct option of \( D = \frac{C - 16}{17} \) or something equivalent to this form, that would be the correct choice.
If we were to approximate:
- As \( C \) is divided by 17 in the correct expression, you may see it written as \( D = \frac{1}{17}C - \frac{16}{17} \). This might indicate that \( \frac{1}{7}C - 16 \) reflects different terms, but this specific formulation is incorrect in the context of the original equation.
Please check if there was an error in the response options provided, or if thereβs an intention to solve different expressions!